Волоконно-оптичні датчики на основі брегівських решіток - Яшин, М. В. (ХНУРЕ, 2023)
The structure, principle of action and application are described. These sensors are capable of measuring a variety of physical parameters, such as temperature, strain, stress, pressure, etc., and they have found applications in many fields of industry, medicine, science, and ecology due to their advantages such as high measurement accuracy and the ability to work under high temperature conditions, moisture, aggressive environments and hard-to-reach places.